IMPLEMENTASI PRINSIP-PRINSIP FILSAFAT EKSISTENSIALISME DALAM KURIKULUM MERDEKA: MENEMUKAN MAKNA DAN KEBEBASAN DALAM BELAJAR - Bora, Bimarto; Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Merdeka Curriculum was introduced as a response to post-pandemic educational challenges, emphasizing flexibility, learner autonomy, and student-centered approaches. This article aims to examine the implementation of existentialist philosophy in the Merdeka Curriculum and its implications for both students and teachers. This study employed a qualitative approach using literature review methods, analyzing primary sources of existentialist philosophy and secondary sources such as journal articles, conference proceedings, and educational policy documents. The findings indicate that existentialist principles freedom, responsibility, and authenticity are reflected in differentiated learning, Project Based Learning (PjBL), Problem Based Learning (PBL), and the Pancasila Student Profile Projects (P5). For students, this approach enhances ownership of learning, supports the search for meaning and authentic identity them. For teachers, it demands a shift in role from knowledge transmitters to facilitators of student existence, although challenges remain regarding administrative workload and mindset transformation. The study concludes that, when viewed through the lens of existentialism, the Merdeka Curriculum has the potential to cultivate a more humanistic, meaningful, and future-oriented educational ecosystem.